2014
DOI: 10.35188/unu-wider/2014/875-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth, poverty, and inequality: The case study of Cameroon

Abstract: The purpose of this paper is to analyse the growth performance of the Cameroonian economy from independence in 1960 to date, and then to use this as a background for the analysis of poverty, inequality, and non-monetary outcomes. The analysis of poverty and inequality uses the microeconomic data from three comparable and nationally representative Cameroonian household surveys that were conducted respectively in 1996, 2001, and 2007. These objectives are complemented by an analysis of the four Demographic Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Third, the decolonization and post-colonial restructuring in Africa embedded a system of Western dominance and subjugation (Frenkel, 2008). Sub-Saharan economies and institutions were weakened or undermined as they came to rely solely on inward investments from former colonial powers (Fambon, 2013). The institutional landscapes that were created following independence treated the new African states as little more than appendages of the colonizers (Fonchingong, 2005).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the decolonization and post-colonial restructuring in Africa embedded a system of Western dominance and subjugation (Frenkel, 2008). Sub-Saharan economies and institutions were weakened or undermined as they came to rely solely on inward investments from former colonial powers (Fambon, 2013). The institutional landscapes that were created following independence treated the new African states as little more than appendages of the colonizers (Fonchingong, 2005).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This failure was because economics were mostly influenced by the French metropolitan administration that setup Cameroon's systems after independence. For example, the 1952 labor code, instituted by colonial authorities, was successively promulgated to other codes in 1967 and 1974 (Fambon, 2013). The only significant modification of the 1974 code was the establishment of rigid labor contracts whereby conditions for dismissal were constraining, in terms of notice, allowances, and administrative procedures.…”
Section: Findings and Analysismentioning
confidence: 99%
“…The results indicated that FDI and economic growth are jointly determined in Nigeria and there is positive feedback from FDI to growth and from growth to FDI. Fambon (2013) investigated the effect of foreign capital inflows (foreign aid and foreign direct investment) on economic growth in Cameroon. The study employed an autoregressive distributive lag approach to the co-integration and time-series data for the period 1980-2008.…”
Section: Athens Journal Of Business and Economicsmentioning
confidence: 99%
“…These illegal activities even though may provide income to the individuals involved, but add very little value to the society and the national economy (Fambon, 2006). c) and Thomas (1992) have defined the sector in two approaches: "the definitional and behavioral".…”
Section: Ghanamentioning
confidence: 99%